Influence of outer membrane c-type cytochromes on particle size and activity of extracellular nanoparticles produced by Shewanella oneidensis - Kjelleberg, Staffan (2013)
The metal-reducing bacterium Shewanella oneidensis is capable of reducing various metal(loid)s and produces nanoparticles (NPs) extracellularly, in which outer membrane c-type cytochromes (OMCs) have been suggested to play important roles. The objective of this study was to investigate the influence of the OMCs, that is, MtrC and OmcA, on the size and activity of the extracellular silver NPs (AgNPs) and silver sulfide NPs (Ag2S NPs) produced by S. oneidensis MR-1. We found that (i) the lack of OMCs on S. oneidensis cell surface decreased the particle size of the extracellular biogenic AgNPs and Ag2S NPs; (ii) the biogenic AgNPs from the mutant lacking OMCs showed higher antibacterial activity; and (iii) the biogenic Ag2S NPs from the mutant lacking OMCs exhibited higher catalytic activity in methylviologen reduction. The results suggest that it may be possible to control particle size and activity of the extracellular biogenic NPs via controlled expression of the genes encoding surface proteins. In addition, we also reveal that in extracellular biosynthesis of NPs the usually neglected non-cell-associated NPs could have high catalytic activity, highlighting the need of novel methods that can efficiently retain extracellular NPs in the biosynthesis processes.